UJI PERFORMANCE BIOFILTER ANAEROBIK UNGGUN TETAP MENGGUNAKAN MEDIA BIOFILTER SARANG TAWON UNTUK PENGOLAHAN AIR LIMBAH RUMAH POTONG AYAM - Said, Nusa Idaman; Firly, Firly (Jurnal Air Indonesia, 2005)
An experiment of anaerobic biofilter using honeycomb plastic media was conducted in semi-pilot scale. This paper describes the pilot plan study of chicken’s slaughterhouse wastewater treatment using anaerobic and aerobic submerged biofilter using honeycomb plastic media. The main research was conducting by continuous operation under condition 4 days, 2 days and 1 day retention time. The result of experiment shows that within the anaerobic process under conditions 1- 4 days retention time, the removal efficiency of COD were 78 – 87 %, BOD were 78 – 89 %, 73 – 83 % , and Total Suspended Solids (TSS) were 83 – 96 % respectively. Using combined anaerobic and aerobic process under same conditions 1 - 4 days retention time shows increasing of removal efficiency. The removal efficiency of COD were 86 – 90 %, BOD were 85 – 90 %, Organics (KMnO4) were 81 – 88 % and Total Suspended Solids (TSS) were 94 – 96 % respectively. The longer retention time has resulted in higher removal efficiency. Kata Kunci : Biofilter anaerobik, media sarang tawon, air limbah, rumah potong ayam.